A population-based prospective study of optic neuritis. (December 2017) - Soelberg, K; Jarius, S; Skejoe, HPB; Engberg, H; Mehlsen, JJ; Nilsson, AC; Madsen, JS; Reindl, M; Wildemann, B; Grauslund, J; Kyvik, KO; Smith, TJ; et al.
Background: Optic neuritis (ON) is often associated with multiple sclerosis (MS). Early diagnosis is critical to optimal patient management. Objective: To estimate the incidence of acute ON and the rates of conversion to MS and antibody-mediated ON. Method: Population-based prospective study was performed in patients with ON from three ophthalmological departments and 44 practicing ophthalmologists from 2014 to 2016. Ophthalmological and neurological examination, magnetic resonance imaging (MRI), determination of aquaporin-4(AQP4)-IgG and myelin-oligodendrocyte glycoprotein (MOG)-IgG were investigated blindly. Results: In all, 63 patients were evaluated and 51 fulfilled the criteria for ON. All were Caucasian, with female:male ratio of 2.2:1 and a median age of 38 years (16–66); 44 (86%) had a single episode of ON (four bilateral), while 7/51 (14%) had recurrent ON. The overall age-specific incidence was 3.28 (2.44–4.31) per 100, 000 person years, 2.02 for men and 4.57 for women. At follow-up, 20 patients met the diagnostic criteria for MS, MRI lesions disseminated in space and time in 17/20 patients. AQP4-IgG was detected in none, MOG-IgG was detected in two patients. Conclusion: The prospective incidence of ON was estimated. MRI enabled a diagnosis of MS in a subgroup of patients. Antibody-mediated ON with specificity for MOG was detected in 4% of cases.